APPLICATION OF ENTREPRENEURIAL VALUES ON INDIE CLOTHING ENTREPRENEUR IN SURAKARTA - Diana, Okta - (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2014)
ABSTRACTThe purpose of this research is: (1) to find out the entrepreneurial values on Indie Clothing entrepreneur in Surakarta (2) to describe the picture of the implementation of the entrepreneurial values on Indie Clothing entrepreneur in Surakarta (3) to uncover the problems that arise as well as problem-solving strategies in running an Indie Clothing businesses.This research is qualitative research strategy with double systematic description. The technique used is the footage of purposive sampling. The technique of data collection is by interview, observation and document analysis. The validity of the data using the technique of triangulation data/sources and triangulation methods. Data analysis using interactive analysis models.Based on the results of the research, it can be concluded (1) entrepreneurial values on Indie Clothing businessman in Surakarta, amongst other things: (a) Able to see opportunities (b) Optimism (c) Are able to take a risk (d) Original: creativity and innovation (e) Commitment (f) Proactive. (2)  implementation of the entrepreneurial values on Indie Clothing businessman in Surakarta, among others: (a) production (b) marketing (c) finance/financial (d) human resources. (3) the problems and solving strategies in running businesses Indie Clothing, problems occurred in running the business of Indie Clothing include: (a) the limitations of venture capital (b) Any production mistakes which led to the quality of the product does not comply with the standard (c) An employee who is irresponsible, dishonest and less competent (d) the existence of the negligence in spending money, the lack of information regarding financial owned (e) An endorsement that is less professional team and imaging characteristics of line of business (f) the existence of a threat from the other party, its strategic location, less effort, lack of parking lots. Steps in problem solving in working Indie Clothing include: (a) borrow from venture capital to the banks and saving (b) controlling production (c) personal Approach towards workers who are less accountable, less competent and less disciplined (d) took note of the financial flows/financial as well as financial control both in production activities as well as private spending (e) marketing by using online media as well as program discounted products. (f) looking for a new location away from the problem, its strategic location and availability of parking lots. Keywords: entrepreneurship, Entrepreneurial values, Indie Clothing